The effect of group art therapy on acculturative and academic stress of Chinese graduate students in South Korea - Yin, Yue; Ko, Kyung Soon (Frontiers in Psychology, 2023)
Background: Research has shown that international students, specifically Chinese graduate students in South Korea, are vulnerable to stress and depression because of various factors. These include environmental changes, economic constraints, interpersonal difficulties, discrimination, and cultural conflict. Objective: This study investigates the effectiveness of group art therapy in reducing acculturative stress and academic stress among Chinese graduate students in South Korea. Method: Thirty participants were recruited and randomly assigned to the experimental (n=15) and control groups (n=15). The experimental group received eight 120-minute sessions of group art therapy. Both groups were tested for acculturative stress (perceived discrimination, homesickness, perceived hate, fear, stress due to change/culture shock) and academic stress (schoolwork stress, future stress, social stress, living environment stress) before and after the art therapy intervention. Results were compared using the Mann-Whitney U test and the Wilcoxon signed-rank test. Results: The results showed that there was a significantly greater reduction in acculturative and academic stress in the experimental than the control group. Conclusion: Group art therapy can provide psychological and emotional support to international students studying abroad.